"Going to Lunch": The Role of Catch Phrases and Language in Constructing a Heteronormative Leadership Culture. (April 2021) - Mungaray, Kimberly R.; Curtin, Nancy J.
This study examines raw focus group data from a previous case study that demonstrated the existence of a heteronormative leadership paradigm, personified in the heteronormative ideal leader who is strong, agentic, charismatic, and typically White and male. The current study corroborated the findings from the previous case study, which contributes to even more profound meaning for the current study's conclusions. For this study, the second author independently analyzed the data using a methodology that combines elements of discourse analysis and conversation analysis to identify what organizational cultural and identity messages are communicated by focus group participants. Through this methodological framework, the researchers found that catch phrases and language were used to construct personal and organizational identities integral to a heteronormative leadership culture despite the organization's stated and intended dedication to being a "pro-woman" firm.